Students’ Comprehension and Difficulties on Reading Descriptive Text at SMA Swasta Pencawan Medan - Herna Sianturi; Christina Siahaan; Syarifah Isma Dinda; Yenita Br Sembiring (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to find out the student's Reading Descriptive Text. The method used in this research is qualitative; the study was conducted at SMA Swasta Pencawan Medan with the samples were 30 students of XI MIA-2. The researcher used multiple-choice with ten questions, reading tests, and interviews. The data collected from the students' scores. The result showed that there is 0 student or 0 % who was categorized excellent, there were two students or 6,67% who were classified as very good, there were seven students or 23,3 % who categorized as good, there were seven students or 23,3% were categorized as fair, there were five students or 16,7 % who were classified unsatisfactory. There were nine students or 30 % who were categorized very poorly. So, from the result, the researcher can conclude that the students were still in the poor category. Keywords: reading, comprehension; reading comprehension problem; descriptive